Symposium 1: E-Teaching: An Essential Prerequisite for Networked E-Learning - Guri-Rosenbilt, Sarah (Proceedings of the International Conference on Networked Learning, 2018)
The discourse on the implementation of the digital technologies and networked learning in higher education settings focuses mainly on students' learning and their ability to connect to information and/or other students rather than on professors' teaching. The little attention paid to the crucial role of teachers in online settings results in a restricted and moderate adaptation of the technologies in higher education worldwide. It is quite clear nowadays that, for e-learning and networked learning to become a dominant learning pattern, technology alone will not suffice. In order to overcome the reluctance of many professors to use extensively the digital technologies, there exists a burning need to develop appropriate incentives and support systems. The little attention paid to the crucial role of teachers in digital networks and online settings results in a restricted and moderate adaptation of the technologies in higher education so far. Of particular importance is an ongoing and just-in-time support. Many institutions acknowledge nowadays the need to recruit in the future a broader range of personnel to complement academic staff in order to implement the technologies more effectively. The roles of teachers in an online environment differ meaningfully from their traditional roles in a classroom setting. To equip professors with tools to use the wide range of capabilities enabled by the new technologies necessitates a conceptual redefinition of the teachers' roles, a well designed training, and ongoing support systems for both students and teachers. The new technologies require the academic faculty to assume new responsibilities and to develop a range of new skills. Academics will have to become in the future reconciled to collaborating with other colleagues and professionals in designing materials and in the teaching process. They will need to learn how to collaborate in a team framework with tutors, editors, instructional designers, television producers, computer experts, graphic production personnel, etc. in developing and delivering their courses, as well as guiding their students to utilize efficiently networked learning. At the same time, teachers will have greater flexibility to choose the teaching styles better suited for their personal strengths and individual preferences. University leaders will have to deliberate how to prepare the new generations of academic faculty to operate in a world where blended courses, shared or dual diplomas, online teaching and networked learning are an integral part of the academic teaching responsibilities. Unquestionably, e-teaching constitutes an essential prerequisite for achieving efficient and fruitful networked learning and e-learning, and it provides multiple domains of investigation that have not been explored yet.